HUBUNGAN STATUS GIZI DENGAN LAMA HARI RAWAT INAP PASIEN ANAK DIARE AKUT - Amin, Muhammad Rizal; Hartoyo, Edi; Marisa, Donna (Berkala Kedokteran, 2016)
Abstract: Good nutritional status can reduce the risk of diarrhea, while children with less or poor nutritional status enables more frequent and more susceptible to diarrhea. The worse the nutrition of a children, the frequency of diarrhea increases. This situation may have a relationship with length of stay. Length of stay of childhood diarrhea is influenced by the childs physical condition (good nutritional status, less, or worse). The purpose of this study is analyzing the relationship between nutritional status and length of stay of pediatric patient on acute diarrhea in Ulin General Hospital Banjarmasin 2014. This study was done by observational analytic with cross sectional approach. Total of 50 samples were obtained by purposive sampling; 2 patients with excess nutritional status, 37 patients with good nutritional status, 8 patients with less nutritional status, and 3 patients with poor nutritional status. Data was analyzed using the Kruskal-Wallis test with a confidence level of 95%  showed that the average length of stay in each nutritional status have no significant value difference (p=0,193). It was concluded that there is no relationship between nutritional status and length of stay of pediatric patient on acute diarrhea in Ulin General Hospital Banjarmasin 2014. Keywords: nutritional status, length of stay, acute diarrhea Abstrak: Status gizi anak yang baik dapat mengurangi risiko terkena penyakit diare, sedangkan anak dengan status gizi kurang atau buruk memungkinkan lebih sering dan lebih mudah terkena diare. Makin buruk gizi seorang anak, ternyata frekuensi diare semakin banyak. Keadaan ini mungkin memiliki hubungan dengan lama hari rawat inap. Hari rawat diare anak salah satunya dipengaruhi oleh kondisi fisik anak (status gizi baik, kurang, atau buruk). Tujuan penelitian ini adalah untuk menganalisis hubungan antara status gizi dengan lama hari rawat inap pasien anak diare akut di RSUD Ulin Banjarmasin tahun 2014. Penelitian ini bersifat observasional analitik dengan pendekatan cross sectional. Sebanyak 50 sampel didapat secara purposive  sampling sesuai kriteria inklusi, 2 pasien  status gizi lebih, 37 pasien status gizi baik, 8 pasien status gizi kurang, dan 3 pasien status gizi buruk. Analisis data menggunakan uji Kruskal Wallis dengan tingkat kepercayaan 95% menunjukkan bahwa rerata lama hari rawat inap di setiap status gizi tidak memiliki perbedaan nilai yang bermakna (p=0,193). Hal ini berarti bahwa tidak terdapat hubungan antara status gizi dengan lama hari rawat inap pasien anak diare akut di RSUD Ulin Banjarmasin Tahun 2014. Kata-kata kunci: status gizi, lama hari rawat inap, diare akut